Crisis del Sistema Jurídico Mexicano: entre la Reforma Penal y los Actores Sociales Contestatarios (Crisis of the Mexican Legal System: Between Penal Reform and Social Actors Protesters) - Alicia Hernández De Gante (Oñati Socio-Legal Series)
Global economic conditions exert pressure on states, particularly for those who are linked to free trade agreements. Mexico, with the risk of being left out of these processes, has made a series of important reforms in its legislation to attract capital and to ensure cheap labor force. The legal system, from 2007, has been particularly reformed, not only to ensure the safety and enforcement of justice, by protecting human rights in their constitutional essence but also to generate expectations for capital investment. These and other reforms, as well as new institutions, have been very far from solving some serious national problems, such as social impoverishment, organized crime and insecurity. Under the law of the strongest, social movements are criminalized and the new players organized in community police and self-defense groups call into question the monopoly of the use of state violence disputing control of areas overwhelmed with violence. At this point, the objective pursued, based on a careful analysis, is to demonstrate the evident crisis and failure of the Mexican legal system, and the need to reform it given the globalization processes.